Adjuvant hormone therapy in postmenopausal patients with locally advanced breast cancer: hope and reality - V. I. Borisov (Опухоли женской репродуктивной системы)
The clinical efficiency of adjuvant hormone therapy has been considered in patients with operable breast cancer in international ran- domized mulricenter studies. The use of aromatase inhibitors versus tamoxifen is shown to considerably improve relapse-free survival and to reduce the risk of distant metastases and contralateral breast cancer.